Comparison of computed tomographic findings in pulmonary mucormycosis and invasive pulmonary aspergillosis. (July 2015) - Jung, J.; Kim, M.Y.; Lee, H.J.; Park, Y.S.; Lee, S.-O.; Choi, S.-H.; Kim, Y.S.; Woo, J.H.; Kim, S.-H.
Abstract: Because there are no available molecular markers for pulmonary mucormycosis (PM), which has low culture sensitivity, early diagnosis and treatment rely heavily on imaging modes such as computed tomography (CT). However, there are limited data comparing CT findings for PM with those for invasive pulmonary aspergillosis (IPA). Adult patients who met the modified criteria for proven and probable PM (over an 11-year period) and IPA (over a 6-year period, owing to the availability of the galactomannan assay) according to the modified European Organization for Research and Treatment of Cancer/Mycosis Study Group definitions were retrospectively enrolled. IPA cases were selected at a 1 : 4 (PM/IPA) ratio. Thoracic CT scans were reviewed by two experienced radiologists blinded to the patients' demographics and clinical outcomes. A total of 24 patients with PM, including 20 (83%) with proven PM and four (17%) with probable PM, and 96 patients with IPA, including 12 (13%) with proven IPA and 84 (87%) with probable IPA, were eventually analysed. The reverse halo sign was more common in patients with PM (54%) than in those with IPA (6%, p < 0.001), whereas some airway-invasive features, such as clusters of centrilobular nodules, peribronchial consolidations, and bronchial wall thickening, were more common in patients with IPA (IPA 52% vs. PM 29%, p 0.04; IPA 49% vs. PM 21%, p 0.01; IPA 34% vs. PM 4%, p 0.003, respectively). The reverse halo sign was more common, and airway-invasive features were less common, in patients with PM than in those with IPA. These findings may help physicians to initiate Zygomycetes -active antifungal treatment earlier.